IMPLEMENTASI PRINSIP POKOK CONVENTION ON THE ELIMINATION OF ALL FORMS DISCRIMINATION AGAINTS WOMEN (CEDAW) DI INDONESIA - Elfia Farida (Faculty of Law, Universitas Diponegoro, 2011)
The CEDAW has been ratified through Law of the Republic Indonesia Number 7 of 1984 The CEDAWemphasis on equality and equity between men and women. The basic principles of CEDAW are substantive equality principle, nory-discrimination principle and State obligation principle. This principles are a framework for formulating strategies enhancing women's rights. This research purpose to describe, explain and analyze implementation of the basic principles of CEDAW in the law and regulations in Indonesia. The research method used is the juridical-normative. The data obtained qualitatively analysed to reveal the truth of the implementation of the basic principles of CEDAW in the law and regulations in Indonesia Indonesia has tried to fulfill those obligations. but was still discriminatory and the apl1cat1on of the basic principles of CEDAW has not been integrated in the law ( such as the Marriage Law, Citizenship Law, Labour Law. Health Law, the Law on Pornography and so on). Therefore, the executive. legislative and judicial of government have to sincerity to integrate the basic principles of CE DAW as a foundation to make the law in every decision-making. Indonesia should immediately implement the basic principles of CEDAW in a systematic, full and integrated into the law. and give priority to the process of legal reform and to synchronized and harmonised in law.